Elimination of bubbles and improvement of the superconducting properties in MgB2 films annealed using electron beam. (30th January 2017) - Xu, Zhuang; Kong, Xiangdong; Han, Li; Pang, Hua; Wu, Yue; Gao, Zhaoshun; Li, Xiaona
Abstract: MgB2 superconducting films can be readily obtained using the electron-beam annealing method. However, many bubbles existing in the film severely damage the surface morphology, which is known as the deleterious current-limiting mechanism. Based on morphology images and energy-dispersive spectroscopy spectra, we found that, during the annealing process, solid Mg-rich layers evaporate to form Mg vapour in the precursor film, resulting in bubbles in the film. By reducing the cycle thickness of the precursor film, we obtained MgB2 films with better properties. The root-mean-square surface roughness was 2.7 nm over a 10 × 10 μ m area for a 100 nm-thick film, and the critical current density at 20 K was increased to 3.8 × 10 6 A cm −2 . These MgB2 films are suitable for fabricating MgB2 superconducting devices.